Differential accumulation of gliadin proteins in wheat grain of RILs grown at two different agroclimatic conditions and their effect on loaf volume - Elangovan, M.; Dholakia, Bhushan B.; Gaikwad, S. M.; Gupta, V. S. (Australian Journal of Crop Science, 2010)
The end use of wheat depends on the quality and quantity of protein accumulated in the grain during the grain filling stage. Gliadin families of proteins are proved to affect the bread making quality (BMQ) by affecting the rheology and functionality of dough. The gliadin accumulation was analysed using Indian genotypes grown in two diverse agro climatic zones. About 16 RILs along with their parents HI977 and HD2329 revealed significant difference in accumulation of all gliadin fractions. High accumulation of alpha and beta gliadin with low level of gamma gliadin was observed for Kota as compared to Pune location. However, this significant difference in gliadin accumulation due to environment, did not affect the loaf volume performance of the RILs at statistically significant level.
Keywords: loaf volume (Lv); RP-HPLC; Wheat protein